INFLUENCE OF TAPIOCA FLOUR CONCENTRATION AND LEGUMES VARIETIES ON CHARACTERISTIC OF BLACK ONCOM WITH Mucor sp AS INOCULUM - Iskandar, Yetti Mulyati; Priatni, Sri; Kardono, L.B.S. (Teknologi Indonesia, 2010)
Oncom is a product prepared by fermenting cooked peanut presscake as substrate mixed with tapioca fl our using Mucor sp as inoculum. The aim of this research is to determine the chemical composition and nutritional contents of black oncom using lupine (Lupinus angustifolius) and pigeon pea (Cajanus cajan) as substrate instead peanuts ( Arachis hypogaea ) to evaluate its potential as a new source of protein. The moisture content, pH, texture, solidness, hardness, mold growth and colour of black oncom fermented product were observed. Various tapioca fl our concentration in amount of 5%, 20% and 35% respectively were mixed on peanuts, lupine and pigeon pea as substrates. The fermentation process was conducted for 48 hours at 30oC.The result revealed that the addition 20% of tapioca to substrate showed the best performance of black oncom product and had good sensory characteristics such as texture, taste, aroma and colour based on the sensory evaluation test.